Papua New Guinea : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2004)
This 2004 Article IV Consultation highlights that Papua New Guinea's macroeconomic performance has improved from mid-2003, helped importantly by the favorable temporary factors that boosted the mineral and agricultural sectors. In 2003, real GDP is estimated to have grown by 2.7 percent, following three years of decline. Coffee and cocoa production benefited from better weather conditions, and production of palm oil, rubber, tea, and copra oil also increased. Papua New Guinea's medium-term economic outlook as outlined in the government's development strategy is to achieve real GDP growth of 2 1\2 percent annually in 2004-09.